From Early Domesticated Rice of the Middle Yangtze Basin to Millet, Rice and Wheat Agriculture: Archaeobotanical Macro-Remains from Baligang, Nanyang Basin, Central China (6700–500 BC) - Deng, Zhenhua; Qin, Ling; Gao, Yu; Weisskopf, Alison Ruth; Zhang, Chi; Fuller, Dorian Q. (PLOS ONE, 2015)
Baligang is a Neolithic site on a northern tributary of the middle Yangtze and provides a long archaeobotanical sequence from the Seventh Millennium BC upto the First Millennium BC. It provides evidence for developments in rice and millet agriculture influenced by shifting cultural affiliation with the north (Yangshao and Longshan) and south (Qujialing and Shijiahe) between 4300 and 1800 BC. This paper reports on plant macro-remains (seeds), from systematic flotation of 123 samples (1700 litres), producing more than 10,000 identifiable remains. The earliest Pre-Yangshao occupation of the sites provide evidence for cultivation of rice (Oryza sativa) between 6300–6700 BC. This rice appears already domesticated in on the basis of a dominance of non-shattering spikelet bases. However, in terms of grain size changes has not yet finished, as grains are still thinner than more recent domesaticated rice and are closer in grain shape to wild rices. This early rice was cultivated alongside collection of wild staple foods, especially acorns (Quercus/Lithicarpus sensu lato). In later periods the sites has evidence for mixed farming of both rice and millets (Setaria italica and Panicum miliaceum). Soybean appears on the site in the Shijiahe period (ca.2500 BC) and wheat (Triticum cf. aestivum) in the Late Longshan levels (2200–1800 BC). Weed flora suggests an intensification of rice agriculture over time with increasing evidence of wetland weeds. We interpret these data as indicating early opportunistic cultivation of alluvial floodplains and some rainfed rice, developing into more systematic and probably irrigated cultivation starting in the Yangshao period, which intensified in the Qujialing and Shijiahe period, before a shift back to an emphasis on millets with the Late Longshan cultural influence from the north.